2019
DOI: 10.1371/journal.pone.0211902
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation of motor cortex enhances running performance

Abstract: Transcranial direct current stimulation (tDCS) is a technique used to modulate neuronal excitability through non-invasive brain stimulation that can enhance exercise performance. We hypothesize that tDCS would improve submaximal running time to exhaustion (TTE) and delay the increase in the rating of perceived exertion (RPE) over time. We also hypothesize that tDCS would not lead to difference in cardiorespiratory responses. We employed a randomized, single-blinded, and counterbalanced design in which 10 train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 45 publications
2
48
0
9
Order By: Relevance
“…Bolzoni, Bączyk, and Jankowska () and Bolzoni, Pettersson, and Jankowska () showed, both in cats and in rats, that the amplitudes of descending volleys evoked by red nucleus stimulation were strongly modified by trans‐cranially applied DC and that these modifications outlasted DC applications by at least 90 min. Several later studies showed that long‐term modifications of neuronal activity by polarization can be observed at the level of the motor cortex (Park, Sung, Kim, Kim, & Han, ) the brain stem nuclei (Bączyk & Jankowska, ) and the spinal cord (Bolzoni & Jankowska, ).…”
Section: Discussionmentioning
confidence: 99%
“…Bolzoni, Bączyk, and Jankowska () and Bolzoni, Pettersson, and Jankowska () showed, both in cats and in rats, that the amplitudes of descending volleys evoked by red nucleus stimulation were strongly modified by trans‐cranially applied DC and that these modifications outlasted DC applications by at least 90 min. Several later studies showed that long‐term modifications of neuronal activity by polarization can be observed at the level of the motor cortex (Park, Sung, Kim, Kim, & Han, ) the brain stem nuclei (Bączyk & Jankowska, ) and the spinal cord (Bolzoni & Jankowska, ).…”
Section: Discussionmentioning
confidence: 99%
“…Benefits have been demonstrated in patients with chronic pain syndromes (Fregni et al, 2006; Fenton et al, 2009; Fagerlund et al, 2015) and neuropsychiatric conditions (Baker et al, 2010; Loo et al, 2012; Palm et al, 2012; Kaski et al, 2014; Bandeira et al, 2016; Breitling et al, 2016), whilst in the healthy population, there is increasing scientific interest in the motor enhancing properties of the technology. Aligning with this trend, an increasing number of commercial companies (Edwards et al, 2017) promote the augmentation of motor abilities with tDCS including greater muscular power output (Okano et al, 2015; Huang et al, 2019), longer athletic endurance (Vitor-Costa et al, 2015; Park et al, 2019) and improved posture and balance (Kaminski et al, 2016; Saruco et al, 2017). This arena is most commonly explored through anodal tDCS to the primary motor cortex (M1), although the precise mechanism of action remains a matter of debate (Giordano et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Le prix abordable et la facilité d'utilisation (connexion Bluetooth avec un smartphone, absence de gel conducteur ou de liquide physiologique pour une bonne conduction et réglages faciles) rendent ce genre d'appareil attractif. Un faible nombre d'articles (deux) avec une très petite population (respectivement 9 et 10 sujets) ont étudié l'utilité de cette appareil dans le sport, et rapportent une amélioration des performances physiques [17,39]. Cependant, il faut reconnaître la principale limite de ce modèle : il ne peut stimuler que les zones motrices (alors que la stimulation du cortex frontal ou dorsolatéral préfrontal a fait énormément de preuves quant à ses effets sur la perception de la douleur) [58].…”
Section: Discussionunclassified
“…En effet, certains auteurs suggèrent qu'elle permettrait d'accentuer la motivation, afin de permettre aux sportifs de puiser plus loin dans leurs efforts [11,12]. D'autres pensent que la STCC pourrait limiter la perception de douleur lors d'activités musculaires intenses [13][14][15][16], même si cela reste controversé [17][18][19]. Il semblerait que la STCC pourrait aussi moduler de manière bénéfique la fatigue supra-spinale [20], ou encore repousser les limitations physiologiques protectrices mise en place par le corps (comme, notamment, pour les contractions excentriques maximales) [21].…”
Section: Introductionunclassified